Analisis Respon dan Faktor-Faktor yang Mempengaruhi Petani terhadap Penerapan Pertanian Organik di Kota Mataram - Utama FR, Aeko Fria; Nursan, Muhammad (Department of Agribusiness, Halu Oleo University, 2020)
The city of Mataram is one of the regions that has the potential for developing organic agriculture and has prepared a policy of using organic materials for farmers in conducting their farming. One of the policies of the Mataram City Government in supporting organic farming practices is to provide assistance in the form of production equipment in the form of an organic fertilizer counter for each farmer group. But in reality, at this time there are still not many farmers who want to do an organic farming system in their farming business. The purpose of this study is to 1) Determine farmers' responses to organic agriculture, and 2) link the factors that encourage farmers to apply organic farming. The method used in this research is descriptive method. This research was conducted in two districts namely Selaparang Subdistrict and Sekarbela Subdistrict, Mataram City, which were selected by purposive sampling. The data in this study are cross section data obtained from interviews with 40 people taken by quota sampling consisting of 20 organic farmers and 20 non-organic farmers. The data collected is then analyzed using a categorical data analysis model. The results showed that, the response of organic farmers to organic farming in the city of Mataram depended on positive results. The response of organic farmers to organic farming in the city of Mataram was positive because respondents thought that the benefits of organic farming on soil fertility were very high, could reduce environmental pollution and could increase increased agriculture. While the response of non-organic farmers to organic farming is in the moderate / less positive range. This causes the complexity of the application of organic agriculture both in terms of fertilization and when spraying pests and diseases. Factors that support farmers in implementing organic farming systems in the city of Mataram are the role of extension workers, approval of agricultural technology and capital. While the factors that hamper farmers involving organic agriculture are farmer prices, prices of organic products which are the same as non-organic products, capital, access to information and access to organic agricultural production.